3 G (x)= X^3 F (x). Find G' (2) , Given That F (2)

Anonymous

From: -
Posts: -
Votes: -
3 g (x)= x^3 f (x). Find g' (2) , given that f (2) = 6 and f ' (2) = 3 . 4 If f (x)= (x^2 + 1)^4 , find f ' (0) .

 

Answer No.1

Anonymous

From: -
Posts: -
Votes: -
3. g'(x) = 3x^2 f(x) + x^3 f'(x) put x = 2 g'(2) = 3*2^2 f(2) + 2^3 f'(2) = 72+24 = 96 4. f'(x) = 8x(x^2 + 1)^3 put x = 0 f'(0) = 0

Answer No.2

Judy Malas

From: US
Posts: 33
Votes: 99
G' = 3x^2 f(x) + x^3 f'(x) g'2 = 12 x 6 + 8 x 3 = 72 + 24 = 96 f' = 4(x^2+1)^3 * (2x) f'(0) = 0

Your Comment/Solution

Post As: Anonymous [Change]
Enter